Aggression Dimensions Among Athletes Practising Martial Arts and Combat Sports - Kostorz, Karolina; Sas-Nowosielski, Krzysztof (Frontiers in Psychology, 2021)
Purpose: The main aim of the research was to analyse aggression dimensions among athletes practising martial arts and combat sports. Material and Methods: There were 219 respondents. The Buss and Perry Aggression Questionnaire (BPAQ) in the Polish adaptation by Siekierka was applied. Results: Martial arts apprentices turned out to present a statistically significantly lower level of hostility (p < 0.001) and of the general aggression index (p = 0.04) than combat sports athletes. It turned out that lower level of aggression was noted in female participants (physical aggression (p < 0.001), verbal aggression (p = 0.004), hostility (p < 0.001), and the general aggression index (p < 0.001). Analysis revealed that the training experience and the training rank did not differentiated the level of the respondents' particular aggression dimensions. Conclusions: It would be advisable to perform parallel analyses in other areas of Poland and take into account the respondents' education and place of residence.